BCL6 BTB‐specific inhibition via FX1 treatment reduces Tfh cells and reverses lymphoid follicle hyperplasia in Indian rhesus macaque (Macaca mulatta). Issue 1 (1st October 2019) - Cai, Yanhui; Watkins, Meagan A.; Xue, Fengtian; Ai, Yong; Cheng, Huiming; Midkiff, Cecily C.; Wang, Xiaolei; Alvarez, Xavier; Poli, Adi Narayana Reddy; Salvino, Joseph M.; Veazey, Ronald S.; Montaner, Luis J.
Abstract: Background: The BTB domain of B‐cell lymphoma 6 (BCL6) protein was identified as a therapeutic target for B‐cell lymphoma. This study compared the pharmacokinetics (PK) of the BCL6 BTB inhibitor (FX1) between mice and macaques, as well as evaluating its lymphoid suppressive effect in uninfected macaques with lymphoid hyperplasia. Materials and Methods: Eight uninfected adult Indian rhesus macaques ( Macaca mulatta ) were used in the study, four animals carrying lymphoid tissue hyperplasia. Plasma FX1 levels were measured by HPLC‐MS/MS. Lymph node biopsies were used for H&E and immunohistochemistry staining, as well as mononuclear cell isolation for flow cytometry analysis. Results: Inhibition of the BCL6 BTB domain with FX1 led to a reduction in the frequency of GC, Tfh CD4 +, and Tfh precursor cells, as well as resolving lymphoid hyperplasia, in rhesus macaques. Conclusions: B‐cell lymphoma 6 inhibition may represent a novel strategy to reduce hyperplastic lymphoid B‐cell follicles and decrease Tfh cells.